Peningkatan Sikap Disiplin dan Hasil Belajar Unjuk Kerja Mata Pelajaran Teknik Pemesinan Bubut Melalui Pembelajaran Project Based Learning - Syarif Ananto (Departement of Mathematics Education, 2022)
The purpose of this study is to improve the attitude of discipline and student performance learning outcomes in Lathe Machining Techniques by using Project Base Learning (PjBL) in class XII TPM-D students Machining Engineering Skills Competencies State Vocational School 2 Surakarta even semester 2019/2020 school year. The research procedure used is Classroom Action Research procedures. Through the learning method Project Base Learning (PjBL) can improve student discipline in Lathe Machining Techniques for students of class XII TPM-D State Vocational School 2 Surakarta even semester 2019/2020 school year from the initial conditions by 34.29% increase in cycle 2 to 100% resulting in an increase by 65.71%. Through the learning method Project Base Learning (PjBL) can improve student performance learning outcomes n Lathe Machining Techniques for students of class XII TPM-D State Vocational School 2 Surakarta even semester 2019/2020 school year from the initial condition of 20% increase in cycle 2 to 100% resulting in an increase by 80%.